Plant-Based Nanomaterials for Contaminated Environs Nanoremediation - Albahnasawi, Ahmed; Alazaiza Motasem, Y. D.; Gürbulak, Ercan; Eyvaz, Murat (Apple Academic Press, 2024)
In the most recent technological-scientific revolution, nanotechnology has rapidly increased in appeal across various industries and academic fields, particularly environmental remediation. For the advancement of innovative nanotechnology, controlled, simple, affordable, and safe nanomaterial synthesis is looked for. Due to the toxic chemicals used or the byproducts created nanomaterial production methods like chemical synthesis are not safe or ecologically benign. A few nanoparticles are also produced as a byproduct of the washing process; these compounds could build up in the soil, water, and air systems and constitute a significant threat to plants, animals, and bacteria. In contrast, it has been shown that employing plants to synthesize nanomaterials is both cost-effective and environmentally friendly. Compared to many other types, plant-based nanoparticles are less toxic, making them intriguing candidates to prevent widespread harm to the microbiome caused by present methods. In the realm of environmental remediation, the usage of plant-based NPs has shown a variety of benefits and uses. Therefore, this chapter aims to examine the current state of knowledge on products made from plant-based nanoparticles for environmental cleanup. The broad use of plant-NP interactions in environmental remediation will also be covered. © 2025 Elsevier B.V., All rights reserved.
Keywords: Environmental cleanup; Green technology; Plant-derived nanoparticles; Public health; Toxicity